Single underwater image enhancement based on adaptive correction of channel differential and fusion - Zhao, Zefeng; Zhou, Zhuang; Lai, Yunting; Wang, Tenghui; Zou, Shujie; Cai, Haohao; Xie, Haijun (Frontiers in Marine Science, 2023)
Clear underwater images are required by many underwater applications, while absorption, scattering and different water conditions will lead to blurring and different color deviations. In order to overcome the limitations of existing color correction and deblurring algorithms, this paper proposes a fusion based image enhancement method for various water areas. We propose two novel image processing methods, including adaptive channel processing deblurring method and color correction method by limiting the histogram mapping interval. Then we take the two images from a single underwater image through these two methods as the input of the fusion framework, and finally obtain a satisfactory underwater image. To prove the effectiveness of the experiment, we tested our method on the public datasets. The results show that our method can adaptively correct colors cast and significantly enhance the details and quality of attenuated underwater images.